"Oooohh ngalai! sudah hilangkah tulah": a healing ritual performance of Bajau Samah Community in Kota Belud, Sabah, Malaysia - Mohd Kipli Abdul Rahman (N/A, 2017)
"Oooohh ngalai! sudah hilangkah tulah": a healing ritual performance of Bajau Samah Community in Kota Belud, Sabah, Malaysia by Mohd Kipli Abdul Rahman